INTERAKSI INSTRUCTIONAL MODEL DAN ENTRY LEVEL TERHADAP MISKONSEPSI MAHASISWA - I Ketut Suandi; Cening Ardina; I Ketut Parnata (Politeknik Negeri Jakarta, 2019)
AbstractLearners have different entry level and have varying misconception. Misconception of learners tend to be resistant and difficult to change. Alternative instructional model need to be developed to reduce students’ misconception. The purposes of this study are: (1) to describe of students’ misconception profile in accounting subjects, (2) to describe the stages of reducing students’ misconception, and (3) to analyze the interaction effect between instructional model and entry level to the students’ misconception. This quasi experimental study uses two-factor measurement with a factorial version of nonequivalent pretest-postest control group design. The Variables in this study are: students’ misconception, instructional model, and entry level. The total samples are 203 students and each treatment decided 29 subjects as analysis unit. Base on the analysis, the results of the study are: (1) The students’ misconception profile varies and occur in the cost concept, entity business concept, and matching concept. (2) The stages of reducing students’ misconception starting from orientation, elicitation, restructuration, application, and review. (3) There is a significant interaction effect between instructional model and entry level to students’ misconceptions. It is suggested that, cooperative instructional model based on entry level can be applied to reduce students’ misconception.Keywords: entry level, misconception, conventional, elicitation, cooperativeAbstrakPeserta didik memiliki entry level yang berbeda dan memiliki miskonsepsi yang bervariasi. Miskonsepsi peserta didik cenderung resisten dan sulit berubah. Model pembelajaran alternatif perlu dikembangkan untuk mereduksi miskonsepsi mahasiswa. Penelitian ini bertujuan: (1) mendeskripsikan profil miskonsepsi mahasiswa dalam pembelajaran akuntansi, (2) mendeskripsikan tahapan mereduksi miskonsepsi mahasiswa, dan (3) menganalisis pengaruh interaktif antara instructional model dan entry level terhadap miskonsepsi mahasiswa. Penelitian kuasi eksperimen ini menggunakan pengukuran dua faktor dengan versi faktorial nonequivalent pretest-posttest control group design. Variabel dalam penelitian ini adalah: miskonsepsi, instructional model, dan entry level. Total sampel yang digunakan sebanyak 203 orang mahasiswa dan masing-masing perlakuan ditetapkan 29 subjek sebagai unit analisis. Berdasarkan hasil analisis, ditemukan hasil-hasil penelitian sebagai berikut: (1) Profil miskonsepsi mahasiswa bervariasi dan terjadi pada konsep harga perolehan, konsep kesatuan usaha, dan konsep mempertemukan. (2) Tahapan mereduksi miskonsepsi mahasiswa mulai dari tahapan orientasi, elicitasi, restrukturisasi, aplikasi, dan review. (3) Terdapat pengaruh interaktif antara instructional model dan entry level terhadap miskonsepsi mahasiswa. Disarankan, model pembelajaran kooperatif berbasis entry level bisa diterapkan untuk mereduksi miskonsepsi peserta didik..Kata kunci: entry level, miskonsepsi, konvensional, elicitasi, kooperatif